Analysis of Factors Influencing the Interest in Cash Waqf of the Bangkalan Community - Nur Abdurrohim; Dzikrulloh (Penerbit Hellow Pustaka, 2025)
This study aims to analyze the factors that influence Bangkalan people's interest in waqf money. Cash waqf is one of the instruments of Islamic philanthropy that has great potential in improving social and economic welfare. However, public participation in cash waqf is still relatively low. This study uses a quantitative method with an exploratory factor analysis (EFA) approach to identify the main factors that contribute to interest in cash waqf. Data were collected through questionnaires distributed to 100 respondents in Bangkalan Regency. The results show that there are three main factors that influence people's interest in waqf money, namely perception, religiosity, and information. The perception factor has the most dominant influence, followed by religiosity and information. This finding indicates that increasing people's understanding of cash waqf through education and socialization can increase their interest in waqf. In addition, religiosity plays an important role in shaping people's awareness of the benefits of cash waqf as social worship. Accurate and easily accessible information also contributes to increasing public trust and participation.